PP62 Is lower life expectancy in Glasgow explained by deprivation: calculating and decomposing life expectancy inequalities within Scotland. (2nd September 2014) - Seaman, R; Popham, F; Leyland, A; Mitchell, R
Abstract : Background: Glasgow's poor health and high levels of deprivation are well documented. Studies comparing Glasgow to similarly deprived cities in England suggest that there is an excess of deaths experienced in Glasgow that cannot be accounted for by deprivation. However within Scotland comparisons are more equivocal suggesting deprivation could explain Glasgow's mortality and lower life expectancy. However limited research has explored the notion of a "Glasgow effect" within Scotland using life expectancy, an intuitive measure that allows a clear quantification of the magnitude of differences. Methods: Sex specific life expectancy with 95% confidence intervals was calculated for the time period 2007–2011 for each Scottish Index of Multiple Deprivation income deprivation decile in Glasgow and in Aberdeen, Dundee and Edinburgh combined (ADE) as defined by local authority. Life expectancy in Glasgow overall and by deprivation decile was compared to ADE and the inequalities decomposed by age. Results: Life expectancy for males and females in the Glasgow population as a whole was lower than ADE. When life expectancy was compared for each income deprivation decile Glasgow's life expectancy was not systematically lower and deprivation accounted for over 90% of the difference in life expectancy. Decomposing the difference in life expectancy by age showed that there is no systematic age pattern in Glasgow's mortality independent of deprivation. Conclusion: Life expectancy is not systematically lower across the Glasgow population compared to ADE, once deprivation has been accounted for. However the most deprived deciles in Glasgow continue to show significantly lower life expectancy because deprivation in Glasgow is more extreme. Why measures of deprivation fail to account fully for Glasgow's excess mortality when being compared to cities outside Scotland remains an unanswered question.